Identifying the process and challenge of drug administration during the Covid-19 pandemic within region in the absence of sufficient evidence: A qualitative study - Hamed Basir Ghafouri; Seyed Amir Tabibzadeh Dezfooli; Niloofar Abazarian; Mahya Naderkhani; Ahmadreza Nasiri; Monireh Faghir Ganji; Alireza Amanollahi (Elsevier, 2024)
Background: The World Health Organization (WHO) has not identified a definitive cure for COVID-19, recommending supportive treatment or antimicrobial therapy based on individual patient needs. This study explores the processes and challenges emergency physicians at Rasul Akram Hospital in Tehran face when prescribing medications with insufficient evidence during the COVID-19 pandemic. Methods: A qualitative study using conventional content analysis. Purposeful sampling with maximum variation was employed until data saturation was achieved. Seventeen participants (5 women, 12 men) aged 32 to 55 underwent individual in-depth interviews. Results: Analysis of the data from the interviews revealed three main categories, 11 subcategories, and 20 themes. Patient-related factors, including mental conditions, fear, and reliance on rumors, significantly influence healthcare decision-making. Financial, cultural, and social challenges faced by patients also impact treatment choices. Factors related to hospitals and companies, such as economic advertising and restrictions, can affect patient care. Physician-related factors, such as adherence to protocols and consideration of traditional medicine, play a key role in treatment decisions. Conclusion: Patient-related, hospital-related, and physician-related factors are essential in shaping treatment decisions in healthcare settings. Understanding and addressing these diverse influences are crucial for providing effective and personalized healthcare. The complexity of decision-making in healthcare, especially during the pandemic, underscores the importance of considering and navigating these various factors to deliver optimal care tailored to patients' needs and preferences.